Quality Assessment of Cancer Pain Clinical Practice Guidelines - Zhang, Zhigang; Cao, Xiao; Wang, Qi; Yang, Qiuyu; Sun, Mingyao; Ge, Long; Tian, Jinhui (Frontiers in Oncology, 2022)
Abstract Introduction: Several clinical practice guidelines (CPGs) for cancer pain have been published, however, the quality of these guidelines has not been evaluated so far. The purpose of this study was to evaluate the quality of CPGs for cancer pain and identify gaps limiting knowledge. Methods: We systematically searched 7 databases, and 12 websites from their inception to July 20, 2021 to include CPGs related to cancer pain. We used the validated Appraisal of Guidelines for Research and Evaluation Instrument II (AGREE II) and Reporting Items for Practice Guidelines in Healthcare (RIGHT) checklist to assess the methodology and reporting quality of eligible CPGs. The overall agreement among reviewers with the intraclass correlation coefficient (ICC) were calculated. The development methods of CPGs, strength of recommendations, and levels of evidence were determined. Results: Eighteen CPGs published from 1996 to 2021 were included. The overall consistency of the reviewers in each domain was acceptable (ICC from 0.76 to 0.95). According AGREE II assessment, only 4 CPGs were determined to be recommended without modifications. For reporting quality, the average reporting rates for all seven domains of CPGs was 57.46%, with the highest domain in domain 3 (evidence, 68.89%), and the lowest domain in domain 5 (review and quality assurance, 33.3%). Conclusion: The methodological quality of cancer pain CPGs fluctuated widely, and the complete reporting rate in some areas is very low. Researchers need to make greater efforts to provide high-quality guidelines in this field to clinical decision-making.